The current state and future outlook of rescue robotics. Issue 7 (6th August 2019) - Delmerico, Jeffrey; Mintchev, Stefano; Giusti, Alessandro; Gromov, Boris; Melo, Kamilo; Horvat, Tomislav; Cadena, Cesar; Hutter, Marco; Ijspeert, Auke; Floreano, Dario; Gambardella, Luca M.; Siegwart, Roland; et al.
Abstract: Robotic technologies, whether they are remotely operated vehicles, autonomous agents, assistive devices, or novel control interfaces, offer many promising capabilities for deployment in real‐world environments. Postdisaster scenarios are a particularly relevant target for applying such technologies, due to the challenging conditions faced by rescue workers and the possibility to increase their efficacy while decreasing the risks they face. However, field‐deployable technologies for rescue work have requirements for robustness, speed, versatility, and ease of use that may not be matched by the state of the art in robotics research. This paper aims to survey the current state of the art in ground and aerial robots, marine and amphibious systems, and human–robot control interfaces and assess the readiness of these technologies with respect to the needs of first responders and disaster recovery efforts. We have gathered expert opinions from emergency response stakeholders and researchers who conduct field deployments with them to understand these needs, and we present this assessment as a way to guide future research toward technologies that will make an impact in real‐world disaster response and recovery.